Implementasi UNCLOS 1982 dalam Mengatasi Pencemaran Laut oleh Pemerintah Indonesia: Studi Kasus Pencemaran Minyak di Wilayah Perbatasan Kabupaten Bintan - Rivaldin Duha; Vifi Mardianti; Zahra Revy Ramadhani (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
There are several issues that should be the focus of the Indonesian and international governments, including marine pollution in the Bintan area. Indonesia's marine environment has various types of natural resources, both biotic and abiotic natural resources, as well as very important resources such as means of communication, recreational media, trade and transportation routes. Therefore, we need to think about how we can overcome these hazards in the future. Various events that have occurred so far in Indonesia, especially in the border area of Bintan Regency, highlight the role of the Indonesian government in protecting Indonesia's maritime areas from various risks of loss and emphasizing the management of natural resources in an orderly and appropriate manner. Therefore, this study was conducted to analyze the strategies and efforts made by the government by implementing UNCLOS 1982 against oil pollution that often occurs in the border area of Bintan Regency.